Rubber composition

By using ethylene-butene-non-conjugated diene copolymer rubber in fuel cell sealing materials, the problems of low-temperature cold resistance and high-temperature sealing are solved, and high extension in a wide temperature range is achieved Longevity and compression resistance to permanent deformation characteristics, suitable for sealing materials for fuel cell isolation parts.

CN119234018APending Publication Date: 2024-12-31NOK CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380040209.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-22
Filing Date
2023-06-16
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing fuel cell sealing materials are insufficient cold resistance under low temperature conditions, and the sealing properties need to be further improved under high temperature conditions, while taking into account the high elongation and compression resistance to permanent deformation characteristics.

Method used

Ethylene-butene-nonconjugated diene copolymer rubber is used as the basis, and 35 to 55 parts by weight of carbon black, 5 to 23 parts by weight of linear hydrocarbon softener and 0.5 to 10 parts by weight of organic peroxide , optimize the size and structure of carbon black particles to ensure fracturing resistance and compression-resistant permanent deformation characteristics in the low to high temperature range.

Benefits of technology

It achieves excellent fracturing resistance and compression-resistant permanent deformation characteristics in a wide temperature range, ensures the long-life performance of the sealing material, and is suitable for sealing materials for fuel cell isolation parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005131909290000071
    Figure BDA0005131909290000071
  • Figure BDA0005131909290000081
    Figure BDA0005131909290000081
  • Figure BDA0005131909290000101
    Figure BDA0005131909290000101
Patent Text Reader

Abstract

A rubber composition in which: (A) 100 parts by weight of a copolymerized rubber polymer comprising at least one of an ethylene-butylene-non-conjugated diene ternary copolymerized rubber, an ethylene-propylene-non-conjugated diene ternary copolymerized rubber, and an ethylene-propylene copolymerized rubber; (B) 35-55 parts by weight of a carbon black having an iodine adsorption amount of 10-25 mg / g and a DBP oil absorption of 30-140 ml / 100 g; (C) 5-23 parts by weight of a linear hydrocarbon softener having a kinematic viscosity at 40 DEG C of 8-500 mm2 / sec and a flow point of-30 DEG C or less; and (D) 0.5-10 parts by weight of an organic peroxide. This rubber composition exhibits resistance to the sulfide in a wide temperature range from low temperature to high temperature, and can sufficiently fulfill the function required as a sealing material even when used as a sealing material, for example, for a fuel cell separator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a rubber composition, and more particularly to a rubber composition suitable for use as a molding material such as a sealing material for a fuel cell separator. Background Art

[0002] Fuel cells have excellent properties such as requiring almost no use of fossil fuels, which require attention to resource depletion, producing almost no noise when generating electricity, and having a higher energy recovery rate than other energy generation equipment. Therefore, they have been put into practical use in many aspects.

[0003] Among them, polymer electrolyte fuel cells (PEFCs) operate at lower temperatures than other types of fuel cells. Therefore, the components that make up the battery do not have to worry about corrosion of the material surface. In addition, they have the characteristic of being able to release higher currents despite operating at low temperatures. They have attracted much attention as a substitute power source for cogeneration of heat and power for household use and for internal combustion engines for vehicles.

[0004] Among the components constituting the PEFC, the insulator generally has a plurality of parallel grooves formed on both sides or on one side of the flat plate, which play the following roles: transmitting electricity generated by the gas diffusion electrodes in the fuel cell unit to the outside, and discharging water generated during the power generation process into the above-mentioned grooves, thereby ensuring that the grooves serve as flow paths for the reaction gas flowing into the fuel cell unit.

[0005] Fuel cell separators having grooves that play the above-mentioned role are required to be more compact. In addition, since a plurality of separators are stacked and used, a separator sealing material having excellent durability and capable of long-term use is required.

[0006] In addition, the electrolyte membrane of PEFC is formed by a polymer membrane such as a polytetrafluororesin membrane having a perfluorosulfonic acid side chain group. Here, when the sealing material is arranged near the electrolyte membrane to make it cross-linked, it is necessary to consider that the electrolyte membrane will not be degraded due to heating during cross-linking. That is, as a sealing material for fuel cells, it is expected to be cross-linked at a relatively low temperature and in a short time.

[0007] As such a sealing material for a spacer, for example, a sealing material using EPDM has been proposed.

[0008] Patent document 1 describes a sealing material composed of a crosslinked product of a rubber composition as an adhesive sealing material for a fuel cell that can be crosslinked at low temperature and has high sealing and bonding reliability. The rubber composition includes: (A) EPDM, (B) an organic peroxide crosslinking agent having a 1-hour half-life temperature of 130°C or less, (C) a crosslinking aid, and (D) an adhesive component that is a resorcinol compound-melamine compound or a silane coupling agent. Comparative Example 4 describes poor results in a 90° peel test and a T-peel test (initial, after immersion in 90°C warm water for 100 hours, and after 1000 hours) when the adhesive component (D) is not present.

[0009] In addition, Patent Document 2 describes that an ethylene α-olefin copolymer is further blended into the rubber composition described in Patent Document 1, and 5 to 30 parts by weight are blended per 100 parts by weight of EPDM. Examples of α-olefins include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, and 1-decene, which are α-olefins having 3 to 10 carbon atoms. It should be noted that an aluminate coupling agent is also described as the above-mentioned (D) component.

[0010] According to the description of the examples using the ethylene·1-octene copolymer whose α-olefin is 1-octene, the tensile strength, elongation at break, 90° peel strength and volume resistivity (insulation property) are increased, and the compounding effect of the ethylene·α-olefin copolymer is emphasized.

[0011] However, one of the issues with fuel cell vehicles is that they need to be designed and controlled in all situations to prevent freezing of the fuel cell stack (FC stack) and system components, such as when starting and driving under low temperature conditions and when left at freezing points after driving, so that they cannot operate normally. Sealing materials are also required to have cold resistance, but EPDM does not have sufficient cold resistance.

[0012] In order to improve the low temperature performance of EPDM, it is well known that the compatibility is improved by adding plasticizers such as oil so that it is rubbery even at low temperatures. However, in this case, new problems such as reduced rubber strength, reduced rubber elastic modulus, kneading properties, dispersibility, and anti-bleeding properties arise. For this purpose, it is also important as a sealing material for spacers. In order to improve the low temperature sealing performance while having the necessary functions, a rubber composition is proposed, which contains 1 to 10 parts by weight of an organic peroxide crosslinking agent with a specified 1-hour half-life temperature relative to 100 parts by weight of ethylene-butene-non-conjugated diene copolymer (Patent Documents 3 to 5). Although the vulcanized molded product of the rubber composition satisfies the low temperature sealing performance, it is required to further improve the sealing performance in the high temperature range.

[0013] Prior art literature

[0014] Patent Literature

[0015] Patent Document 1: Japanese Patent Application Publication No. 2009-94056

[0016] Patent Document 2: Japanese Patent Application Publication No. 2011-249283

[0017] Patent Document 3: WO2019 / 003884

[0018] Patent Document 4: Japanese Patent Application Publication No. 2017-183162

[0019] Patent Document 5: Japanese Patent Application Publication No. 2021-086791

[0020] Patent Document 6: Japanese Patent Application Publication No. 2011-213822 Summary of the invention

[0021] Technical problem to be solved by the invention

[0022] The present invention is completed in view of the above-mentioned problems. The present invention provides a rubber composition whose sulfide shows resistance in a wide temperature range from low temperature to high temperature, and when used as a sealing material, such as a sealing material for a fuel cell insulator, it can also fully meet the functions required as a sealing material.

[0023] Solutions to Solve Problems

[0024] The object of the present invention is achieved by the following rubber composition, wherein the rubber composition contains 35 to 55 parts by weight of (B) carbon black having an iodine adsorption amount of 10 to 25 mg / g and a DBP oil absorption amount of 30 to 140 ml / 100 g, 5 to 23 parts by weight of (C) a kinematic viscosity at 40° C. of 8 to 500 mm / s, relative to 100 parts by weight of (A) a copolymer rubber polymer composed of at least one of an ethylene-butene-non-conjugated diene tertiary copolymer rubber, an ethylene-propylene-non-conjugated diene tertiary copolymer rubber and an ethylene-propylene copolymer rubber, 2 / sec, a linear hydrocarbon softener having a pour point of -30°C or lower, and 0.5 to 10 parts by weight of (D) an organic peroxide.

[0025] Effects of the Invention

[0026] For example, in a sealing component for a fuel cell, it is required to take into account the contradictory physical properties such as high elongation and compression set resistance. In the rubber composition of the present invention, these physical properties can be taken into account by optimizing the size of the carbon black particles and the size of the structure. That is, by adding a specified amount of carbon black having a specified iodine adsorption amount and DBP oil absorption, the obtained vulcanized molded product can exert the following excellent effects: while ensuring the pressure crack resistance (high ductility), the compression set resistance, which is the main reason for the long life, is excellent in a wide temperature range from low temperature to high temperature. DETAILED DESCRIPTION

[0027] As the polymer, for the purpose of balancing heat resistance, cold resistance, durability, temperature dependence of spring constant, and repulsive stress, a polymer consisting of at least one selected from EBDM (ethylene / butene / non-conjugated diene terpolymer), EPDM (ethylene / propylene / non-conjugated diene terpolymer), and EPM (ethylene / propylene copolymer) is used. That is, any one of EBDM, EPDM, and EPM may be used alone or in combination, preferably in the form of a mixture of EBDM and EPDM, and a copolymer rubber polymer may be used in which EBDM is 70% by weight or more in the total amount of EBDM and EPDM. Each copolymer rubber polymer is typically in a solid state.

[0028] In addition, the ethylene content in the copolymerized rubber polymer is preferably 40 to 60% by weight. If the ethylene content ratio is less than this range, the rubber property is reduced, and it is sometimes difficult to meet the elongation and tensile properties required for the sealing component. On the other hand, if the ethylene content ratio is more than this range, there is a tendency for low temperature properties to deteriorate. In addition, from the viewpoint of acid resistance and water resistance in the working environment of the fuel cell, it is preferred to use an EPDM polymer. From the viewpoint of low temperature sealing, it is preferred to use an EBDM polymer.

[0029] EBDM has a copolymer composition of 30 to 95 wt% of structural units derived from ethylene (preferably 40 to 95 wt%), 4.9 to 49.9 wt% of structural units derived from butene (preferably 4.9 to 35 wt%), and 0.1 to 20 wt% of structural units derived from non-conjugated dienes (preferably 1 to 15 wt%). 5 -2-methyl-s-indacen-1-yl)silanetitanium(II)1,3-pentadiene((tert-butylamido)dimethyl(η 5The polymerization was performed using metallocene compounds such as 2-methyl-s-indacen-1-yl)silane titanium(II)1,3-pentadine as polymerization catalysts.

[0030] This EBDM is described in Patent Document 6, for example. As butene, 1-butene is mainly used, and as non-conjugated diene, cyclic or chain non-conjugated diene such as 5-ethylidene-2-norbornene and 5-vinyl-2-norbornene can be used, preferably cyclic non-conjugated diene. From the viewpoint of low temperature setting, these non-conjugated dienes can be used in an amount of about 1 to 20% by weight, preferably about 3 to 15% by weight of EBDM. In fact, commercially available products such as Mitsui Chemicals EBT can be used directly.

[0031] As EPDM, ethylene, propylene, and non-conjugated diene ternary copolymer rubber polymers can be used. As non-conjugated dienes, dicyclopentadiene, 1,4-hexadiene, dicyclooctadiene, methylene norbornene, vinyl norbornene, ethylidene norbornene, etc. can be copolymerized in small amounts. Its Mooney viscosity ML 1+4 (125°C) is about 25 to 80, preferably about 25 to 70. As EPM, ethylene-propylene copolymer rubber polymer can be used.

[0032] Carbon black, a linear hydrocarbon softener and an organic peroxide are blended with the copolymerized rubber polymer to form a rubber composition. It should be noted that when a bifunctional (meth)acrylate monomer is used as an essential component in Patent Document 5, the elongation may deteriorate at high temperatures as shown in the reference examples described below.

[0033] As carbon black, iodine adsorption is 10 to 25 mg / g, preferably 10 to 20 mg / g, and DBP oil absorption is 30 to 140 ml / 100 g, preferably 30 to 110 ml / 100 g, and the carbon black is used in a ratio of 35 to 55 parts by weight, preferably 40 to 55 parts by weight per 100 parts by weight of copolymer rubber polymer.

[0034] Here, iodine adsorption and DBP oil absorption are representative indicators of carbon black properties. The iodine adsorption is a value measured based on JIS K6221 corresponding to ISO 1304, and the DBP oil absorption is a value measured based on method A (mechanical method) of JIS K6221 corresponding to ISO 4656.

[0035] The iodine adsorption is an indicator of the total specific surface area including the pores of carbon black. In addition, the DBP oil absorption indirectly quantifies the structure by measuring the void ratio between each aggregate, which has a positive correlation with the structure.

[0036] If carbon black having an iodine adsorption amount smaller than the above-mentioned range is used, a large amount of carbon black must be added in order to ensure the reaction force used for sealing due to the increase in hardness, resulting in deterioration of the compressive strain. On the other hand, if carbon black having an iodine adsorption amount larger than the above-mentioned range is used, or if carbon black having a DBP oil absorption amount outside this range is used, the sealing performance under high temperature conditions is reduced.

[0037] In addition, when carbon black is used in a ratio other than this, the sealing performance under high temperature conditions will also be reduced.

[0038] As the linear hydrocarbon softener, about 5 to 23 parts by weight, preferably about 10 to 21 parts by weight, can be used per 100 parts by weight of the copolymerized rubber polymer. 2 / sec. From the viewpoint of volatility, a straight-chain hydrocarbon softener having a flow point of -30°C or less is preferably used, and a liquid polyα-olefin oligomer is preferably used. For example, commercially available products such as DURASYN170 manufactured by INEOS Singapore Pte. Ltd. and DianaProcess Oil PW-380 manufactured by Idemitsu Kosan can be used directly. The kinematic viscosity here is measured in accordance with JIS K2283 corresponding to ISO 2909 and ISO 3104. By adding a straight-chain hydrocarbon softener, the kneading property, the suppression of oozing out, the anti-crack property in a wide temperature range from low temperature to high temperature, and the low elastic attenuation (low settling) are good. When the softener is used in a proportion greater than the above range, for example, the compression set characteristics at a low temperature such as -30°C are deteriorated. On the other hand, when the softener is used in a proportion less than the above range, the elongation at high temperature is reduced.

[0039] Examples of organic peroxides include dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, di-tert-butyl peroxide, di-tert-butylperoxy-3,3,5-trimethylcyclohexane, and tert-butyl hydroperoxide. It is preferred to use an organic peroxide having a 1-hour half-life temperature of 110° C. to 130° C. Here, the 1-hour half-life temperature refers to a temperature at which the half-life is 1 hour in the half-life temperature, which is an index indicating the decomposition temperature of the organic peroxide. The lower the 1-hour half-life temperature, the easier it is for the organic peroxide to decompose at low temperatures.

[0040] As such an organic peroxide having a one-hour half-life temperature, it is preferable to use a peroxyketal or a peroxyester having a one-hour half-life temperature of 110° C. to 130° C., preferably a peroxyketal.

[0041] Examples of the peroxyketal include n-butyl-4,4-di(tert-butylperoxy)valerate, 2,2-di(tert-butylperoxy)butane, 2,2-di[4,4-bis(tert-butylperoxy)cyclohexyl]propane, 1,1-di(tert-butylperoxy)cyclohexane, di(3,5,5-trimethylhexanoyl)peroxide, 1,1-di(tert-hexylperoxy)cyclohexane, 1,1-di(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, and 1,1-di(tert-butylperoxy)-2-methylcyclohexane.

[0042] In addition, as peroxyesters, for example, tert-butyl peroxybenzoate, tert-butyl peroxyacetate, tert-hexyl peroxybenzoate, tert-butyl peroxy-2-ethylhexyl monocarbonate, tert-butyl peroxylaurate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxymaleate, tert-hexyl peroxyisopropyl monocarbonate, etc. can be used.

[0043] The crosslinking agent may be added in an amount of 0.5 to 10 parts by weight, preferably 4.5 to 8.5 parts by weight per 100 parts by weight of the copolymerized rubber polymer. By setting the amount in the above range, it is possible to prevent the foaming from failing during vulcanization, and the crosslinking density is good, so that sufficient physical properties can be easily obtained.

[0044] In addition, a crosslinking accelerator may be contained as required. As the crosslinking accelerator, triallyl isocyanurate, triallyl cyanurate, liquid polybutadiene, N,N'-m-phenylene bismaleimide, trimethylolpropane trimethacrylate, etc. can be used. By adding a crosslinking accelerator in an appropriate amount, the crosslinking efficiency can be improved, and the heat resistance or mechanical properties can also be improved.

[0045] In addition to the above-mentioned components, the rubber composition may contain, as necessary, appropriately added compounding agents commonly used in the rubber industry, such as an antioxidant, a vulcanization aid, and an acid acceptor.

[0046] As the antioxidant, for example, poly-2,2,4-trimethyl-1,2-dihydroquinoline, 2-mercaptobenzimidazole, etc. can be used. As the vulcanization aid, for example, stearic acid can be used. As the acid acceptor, for example, divalent metal oxides or hydroxides, hydrotalcite, etc. can be used.

[0047] The rubber composition can be prepared by kneading various materials using a kneading machine such as a single-screw extruder, a twin-screw extruder, a roll, a Banbury mixer, a kneader, or a high-shear mixer.

[0048] The vulcanization molding is performed by primary vulcanization at about 150 to 230° C. for about 0.5 to 30 minutes and, if necessary, oven vulcanization (secondary vulcanization) at about 150 to 250° C. for about 0.5 to 24 hours.

[0049] Example

[0050] Next, the present invention will be specifically described by way of examples. It should be noted that the present invention, including its effects, is not limited to the examples.

[0051] Example 1

[0052]

[0053]

[0054] The above components were kneaded using a kneader and an open roll, and the kneaded product was vulcanized at 180° C. for 10 minutes and then oven-vulcanized at 150° C. for 24 hours (secondary vulcanization) to prepare a sample sheet with a thickness of 2 mm.

[0055] The following properties of the obtained sulfide were measured and evaluated.

[0056] Elongation test at high temperature: According to JIS K-6251 standard corresponding to ISO37, the elongation at 95°C is measured using a sample sheet. 120% or more is evaluated as ○, and 119% or less is evaluated as ×

[0057] High temperature compression set: Based on JIS K-6262, which corresponds to ISO 815-1, a material consisting of three laminated sample sheets was placed in air at 130°C for 24 hours and evaluated as ◎ for 5% or less, ○ for 6% or more and 10% or less, and × for 11% or more

[0058] Low temperature compression set: Based on JIS K-6262, which corresponds to ISO 815-1, a material consisting of three laminated sample sheets was placed in -30°C air for 24 hours and measured. A value of 30% or less was evaluated as ◎, a value of 31% or more and 40% or less was evaluated as ○, and a value of 41% or more was evaluated as ×

[0059] Low temperature elastic recovery test: Using JIS K-6261 standard corresponding to ISO 2921, measuring TR-10 value and TR-70 value

[0060] TR-10 values ​​of -40°C or less were evaluated as ○, and values ​​of -39°C or more were evaluated as ×

[0061] TR-70 values ​​of -60°C or less were evaluated as ○, and values ​​of -59°C or more were evaluated as ×

[0062] Example 2

[0063] In Example 1, the same amount (50 parts by weight) of MT carbon black (Termax LSR N990 manufactured by Cancarb; iodine adsorption 10 mg / g, DBP oil absorption 38 ml / 100 g) was used as carbon black.

[0064] Comparative Example 1

[0065] In Example 1, the same amount (50 parts by weight) of FT carbon black (Seast TA manufactured by Tokai Carbon Products; iodine adsorption: 18 mg / g, DBP oil absorption: 19 ml / 100 g) was used as carbon black.

[0066] Comparative Example 2

[0067] In Example 1, the same amount (50 parts by weight) of FEF carbon black (Showblack N550 manufactured by Showa Cabot KK; iodine adsorption: 44 mg / g, DBP oil absorption: 115 ml / 100 g) was used as carbon black.

[0068] Comparative Example 3

[0069] In Example 1, the same amount (50 parts by weight) of SRF carbon black (Seast G-SVH manufactured by Tokai Carbon Products; iodine adsorption: 30 mg / g, DBP oil absorption: 140 ml / 100 g) was used as carbon black.

[0070] Comparative Example 4

[0071] In Example 1, the same amount (50 parts by weight) of SRF carbon black (Seast GS manufactured by Tokai Carbon Products; iodine adsorption amount 26 mg / g, DBP oil absorption amount 68 ml / 100 g) was used as carbon black.

[0072] Example 3

[0073] In Example 1, the amount of carbon black was changed to 40 parts by weight.

[0074] Comparative Example 5

[0075] In Example 1, the amount of carbon black was changed to 30 parts by weight.

[0076] Comparative Example 6

[0077] In Example 1, the amount of carbon black was changed to 60 parts by weight.

[0078] Comparative Example 7

[0079] In Example 1, the amount of carbon black was changed to 70 parts by weight.

[0080] Example 4

[0081] In Example 2, the amount of the softener was changed to 10 parts by weight.

[0082] Example 5

[0083] In Example 2, the amount of the softener was changed to 22 parts by weight.

[0084] Comparative Example 8

[0085] In Example 2, the amount of the softener was changed to 24 parts by weight.

[0086] Reference example

[0087] In Example 1, 2.5 parts by weight of 1,6-bis(acryloyloxy)hexane as a bifunctional acrylate monomer was further used.

[0088] The results obtained in the above examples, comparative examples and reference examples are shown in the following Tables 1 and 2.

[0089] Table 1

[0090]

[0091] Table 2

[0092]

[0093] Industrial Applicability

[0094] The rubber composition of the present invention can ensure resistance to compression cracking (high elongation) and at the same time has excellent resistance to compression set, which is the main reason for its long life, in a wide temperature range from low temperature to high temperature. Therefore, it can be effectively used as a sealing material, such as a sealing material for fuel cell insulators.

Claims

1. A rubber composition, wherein: The invention relates to a copolymer rubber polymer composed of at least one of (A) an ethylene-butene-non-conjugated diene terpolymer rubber (EBDM), an ethylene-propylene-non-conjugated diene terpolymer rubber (EPDM) and an ethylene-propylene copolymer rubber (EPM), 35 to 55 parts by weight of (B) carbon black having an iodine adsorption amount of 10 to 25 mg / g and a DBP oil absorption amount of 30 to 140 ml / 100 g, 5 to 23 parts by weight of (C) a carbon black having a kinematic viscosity at 40° C. of 8 to 500 mm 2 / sec, a linear hydrocarbon softener having a pour point of -30°C or lower, and 0.5 to 10 parts by weight of (D) an organic peroxide.

2. The rubber composition according to claim 1, wherein A mixture of EBDM and EPDM is used, wherein EBDM is mixed in a ratio of 70 wt % or more in the total amount of EBDM and EPDM.

3. The rubber composition according to claim 1, wherein (C) Kinematic viscosity at 40°C is 8 to 500 mm 2 / sec, and a straight-chain hydrocarbon softener with a pour point of -30°C or below is a liquid polyolefin oligomer.

4. The rubber composition according to claim 1, wherein (D) The organic peroxide is an organic peroxide having a one-hour half-life temperature of 110 to 130°C.

5. The rubber composition according to claim 1, wherein The rubber composition is used as a molding material for a sealing material.

6. A sealing material which is a vulcanized molded product of the rubber composition according to claim 5.

7. The sealing material according to claim 6, wherein The sealing material is used as a sealing material for a fuel cell separator.